Hepatitis C screening: Getting it right1. Issue 4 (24th December 2012) - Edlin, Brian R.
Abstract Hepatitis C is the most prevalent bloodborne viral disease in the United States and the deadliest. This year, the U.S. Preventive Services Task Force (USPSTF) will update its 2004 hepatitis C guideline, which recommends against screening asymptomatic adults for hepatitis C. This guideline has hampered public health efforts to encourage screening and identify and refer infected persons for care by declaring that such interventions were not supported by the evidence. A draft revision of the guideline, released on November 26, 2012, concludes that testing persons born between 1945 and 1965 probably has at least a small net benefit, but stops short of definitively recommending that this cohort be screened. This article examines the Task Force's process for writing its guidelines. It recommends that the Task Force adopt a balanced approach to evaluating the benefits and harms of screening; use the preponderance of the evidence as a standard for evaluating interventions that target serious public health problems; be transparent about the value judgments that go into its decisions; consider the wide variation in disease prevalence in diverse patient populations; and recommend screening asymptomatic adults for hepatitis C. Conclusion: By taking a broader view of the evidence, the Task Force can write new guidelines that will serve efforts to curb the hepatitis C epidemic, rather than frustrate them. (HEPATOLOGY 2013)